2024
DOI: 10.1111/bjet.13481
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study on practising listening comprehension skills in high‐immersion virtual reality

Yongluan Ye,
Regina Kaplan‐Rakowski

Abstract: Holding learners' attention is challenging, especially when they are asked to listen to long passages. High‐immersion virtual reality (VR) can immerse learners in listening tasks, even in such complex languages as Chinese. This exploratory study examined the effect of VR on 43 Chinese language learners' listening comprehension, enjoyment, sense of presence, and cognitive load. Participants were self‐selected into two groups without knowing the purpose of the study or the details of their activity. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…The language learning study revealed that the combination of various networking strategies, such as individual assignments, interactions with bots, pair work, group work, simulations, and working with a teacher, contributed to significant improvements in participants' speaking, listening, vocabulary, and overall language proficiency. These findings support the notion that immersive and collaborative learning experiences in virtual worlds can facilitate authentic communication and negotiation of meaning, which are essential for language acquisition [11,37,40,69].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The language learning study revealed that the combination of various networking strategies, such as individual assignments, interactions with bots, pair work, group work, simulations, and working with a teacher, contributed to significant improvements in participants' speaking, listening, vocabulary, and overall language proficiency. These findings support the notion that immersive and collaborative learning experiences in virtual worlds can facilitate authentic communication and negotiation of meaning, which are essential for language acquisition [11,37,40,69].…”
Section: Discussionsupporting
confidence: 80%
“…Virtual reality has also been shown to enhance learners' listening comprehension [40]. Kim et al [41] examined the impact of virtual reality on Korean language learners' listening comprehension and reported positive results, with VR-based instruction leading to better listening performance and increased learner motivation.…”
Section: Virtual Reality and Language Acquisitionmentioning
confidence: 99%